The prince of jockeys : the life of Isaac Burns Murphy - McDaniels, Pellom, III (University Press of Kentucky, 2013)
Isaac Burns Murphy (1861-1896) was one of the most dynamic jockeys of his era. Still considered one of the finest riders of all time, Murphy was the first jockey to win the Kentucky Derby three times, and his 44 percent win record remains unmatched. Despite his success, Murphy was pushed out of Thoroughbred racing when African American jockeys were forced off the track, and he died in obscurity. The author offers a biography of this celebrated athlete, whose life spanned the Civil War, Reconstruction, and the adoption of Jim Crow legislation. Despite the obstacles he faced, Murphy became an important figure - not just in sports, but in the social, political, and cultural consciousness of African Americans.